2018
DOI: 10.1182/bloodadvances.2018018408
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated immune suppression by antigen modulation is antigen-specific

Abstract: Alloantibodies developing after exposure to red blood cell (RBC) alloantigens can complicate pregnancy and transfusion therapy. The only method currently available to actively inhibit RBC alloantibody formation is administration of antigen-specific antibodies, a phenomenon termed antibody-mediated immune suppression (AMIS). A well-known example of AMIS is RhD immune globulin prophylaxis to prevent anti-D formation in RhD− individuals. However, whether AMIS is specific or impacts alloimmunization to other antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 60 publications
2
49
0
Order By: Relevance
“…The ability of some IgG subclasses (i.e., IgG2a, IgG2b, and IgG2c) to enhance alloimmunity to an RBC antigen contradicts the current "dual effect" model, in which IgG against soluble antigens enhances immunity whereas IgG against an RBC alloantigen suppresses (17). The dual effect model has been based upon numerous reports in which IgG can enhance responses to soluble antigens, combined with separate reports in multiple animal models that IgG against RBC antigens is suppressive (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and the well-known suppressive effects of anti-RhD in humans. In particular support of the dual effect model, Enriquez-Rincon and Klaus reported that the same monoclonal antibodies (against a hapten) enhance humoral immunity to a haptenated soluble protein but suppress responses to haptenated RBCs (30).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of some IgG subclasses (i.e., IgG2a, IgG2b, and IgG2c) to enhance alloimmunity to an RBC antigen contradicts the current "dual effect" model, in which IgG against soluble antigens enhances immunity whereas IgG against an RBC alloantigen suppresses (17). The dual effect model has been based upon numerous reports in which IgG can enhance responses to soluble antigens, combined with separate reports in multiple animal models that IgG against RBC antigens is suppressive (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and the well-known suppressive effects of anti-RhD in humans. In particular support of the dual effect model, Enriquez-Rincon and Klaus reported that the same monoclonal antibodies (against a hapten) enhance humoral immunity to a haptenated soluble protein but suppress responses to haptenated RBCs (30).…”
Section: Discussionmentioning
confidence: 99%
“…SRBC or SRBC conjugated to haptens such as trinitrophenyl (TNP) or 4‐hydroxy‐3‐nitrophenylacetyl (NP) has frequently been used 7,9,36‐42 . More recently, murine transgenic erythrocytes expressing the entire human KEL glycoprotein (KEL‐RBC), 43,44 hen egg lysozyme in sequence with ovalbumin (OVA) and the complete human Duffy b transmembrane protein (HOD‐RBC), 45‐49 or both HOD and KEL antigens 50 were used as antigen.…”
Section: Which Types Of Responses Are Suppressed By Igg?mentioning
confidence: 99%
“…More recently, splenic germinal centre B cells as well as IgG‐producing long‐lived plasma cells in the bone‐marrow were shown to be suppressed 40 . Also primary serum IgM and IgG responses to xenogeneic 39‐41,54 as well as to allogeneic 43‐50 erythrocytes are suppressed by IgG.…”
Section: Which Types Of Responses Are Suppressed By Igg?mentioning
confidence: 99%
See 1 more Smart Citation
“…We find it unlikely that this mechanism can explain the complete suppression of antibody responses to all epitopes on SRBC. This would require that trogocytosis destroys all erythrocytes and in experimental systems using transferred allogeneic erythrocytes these remain intact in the circulation for hours or days during conditions where trogocytosis has removed specific epitopes ( 20 , 37 ).…”
Section: Discussionmentioning
confidence: 99%